If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 4) = -6x Reorder the terms: -5(4 + x) = -6x (4 * -5 + x * -5) = -6x (-20 + -5x) = -6x Solving -20 + -5x = -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -20 + -5x + 6x = -6x + 6x Combine like terms: -5x + 6x = 1x -20 + 1x = -6x + 6x Combine like terms: -6x + 6x = 0 -20 + 1x = 0 Add '20' to each side of the equation. -20 + 20 + 1x = 0 + 20 Combine like terms: -20 + 20 = 0 0 + 1x = 0 + 20 1x = 0 + 20 Combine like terms: 0 + 20 = 20 1x = 20 Divide each side by '1'. x = 20 Simplifying x = 20
| s=2*2.14rh | | -3(7n-4)+4n= | | (3y+1)+25= | | 7.7(x-2)=-0.3x+40.6 | | -81=-9k | | 10x-5x=5 | | -8=a+3 | | -5(n-1)-4h= | | 1x^2-3x+2=0 | | -2(9p+5)= | | y=.75x+2 | | 6(d+1)= | | 6(2x+3)=-9 | | 3y-7+5y-9= | | -3(x-5)=3(x-1) | | -6(2+3)+52= | | 16y-22y= | | A=1/2*10(6+15) | | x^2=-5 | | x^2-25=2x | | 5(2+x)+2x=20-(2x+6) | | 3x-6x+2= | | x-7x+29=0 | | 10-8x=86-22x | | 0.8x+.18=.3(x+.2) | | 14x^5+6x^3= | | 10-8x=86-26x | | x^2+24x+106=0 | | 14x+7x-18=0 | | 3q+11+8q= | | 9x+3=8-6x | | -9(t+6)=0 |